PENGARUH GAMIFICATION MARKETING DAN INFLUENCER MARKETING TERHADAP CUSTOMER LOYALTY PLATFORM MARKETPLACE SHOPEE (STUDI PADA MAHASISWA UNIVERSITAS RIAU) - Febriosa, Dela; Heriyanto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to examine the influence of gamification marketing and influencer marketing on customer loyalty toward the Shopee marketplace platform, focusing on students from the University of Riau as respondents. The research adopts a quantitative approach, involving 384 Shopee users selected through a non-probability sampling technique using purposive sampling. Data were collected through a questionnaire that had been tested for validity and reliability. The data analysis was performed using both simple and multiple linear regression methods with SPSS version 25. The statistical tests conducted in this study include validity and reliability tests, multicollinearity and heteroscedasticity tests, simple linear regression, t-test, multiple linear regression, F-test, and coefficient of determination (R²). The results indicate that both gamification marketing (X1) and influencer marketing (X2) have a positive and significant effect on customer loyalty (Y). These findings indicate that marketing strategies integrating gamification elements—such as social interaction features, reward systems, and interactive challenges, combined with the strategic implementation of influencer marketing, play a vital role in enhancing customer loyalty on the Shopee platform. Therefore, companies are encouraged to continue innovating and strengthening collaborations with influencers to maintain customer loyalty and competitiveness. Keywords: Gamification Marketing, Influencer Marketing, Customer Loyalty, Marketplace